2020
DOI: 10.1007/s12147-020-09257-0
|View full text |Cite
|
Sign up to set email alerts
|

“Women and “Ideal” Women”: The Representation of Women in the Construction Industry

Abstract: Increased female participation has been highlighted as necessary to fill a labor shortage in the construction industry, but also to promote equality and efficiency. Despite initiatives to recruit women, the industry remains one of the most gender-segregated industries in the world. Increased knowledge about gender has been identified as needed to change the status quo. The aim of this study is to contribute with new insights into gender in construction by exploring how women in the industry are discursively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…This conclusion is drawn in conjunction with the relational and environmental dimension discussed below, which indicates that the construction industry is becoming increasingly accepting and supportive of women [18]. Most of the international studies also reported that although the culture in construction is persistently male, a positive shift in attitudes and a supportive environment is taking place [58,[61][62][63]. As such, women's empowerment can be achieved by taking personal initiative to fully utilise the positive and supportive environment around them, while overcoming other long-standing relational and environmental barriers.…”
Section: Conclusion 2: Capacity Building Based On Skill and Knowledgementioning
confidence: 88%
See 1 more Smart Citation
“…This conclusion is drawn in conjunction with the relational and environmental dimension discussed below, which indicates that the construction industry is becoming increasingly accepting and supportive of women [18]. Most of the international studies also reported that although the culture in construction is persistently male, a positive shift in attitudes and a supportive environment is taking place [58,[61][62][63]. As such, women's empowerment can be achieved by taking personal initiative to fully utilise the positive and supportive environment around them, while overcoming other long-standing relational and environmental barriers.…”
Section: Conclusion 2: Capacity Building Based On Skill and Knowledgementioning
confidence: 88%
“…An international study [59] also pointed out the importance of running self-esteem workshops for women to learn to face and handle conflicts in predominantly male workspaces, so an overall work enjoyment can be better achieved. In fact, a study in Sweden reported that women in construction have learnt that they need to "be able to either laugh at or ignore some of the jokes that men may tell at work" [61] (p. 5) and they become "less sensitive to male dominance and discrimination" [61] (p. 5).…”
Section: Conclusion 1: Focus On the Pleasures Of Work And Resilience ...mentioning
confidence: 99%
“…For example, women, older people, and migrants are especially likely to face barriers in employment [ 48 ]. In industrial sectors of the labor market, women are underrepresented, and may be confronted with negative stereotypes toward women in industry [ 81 ]. One-third of the unemployed population of working age in Germany are migrants or descendants of migrants [ 13 ].…”
Section: Employment Patterns Gender Roles and Institutional Influencementioning
confidence: 99%
“…294). White, cisgender, able‐bodied men are considered “ideal workers,” because it is assumed that they are more committed to work because giving birth or child‐rearing responsibilities are not expected of them (Williams, 2000) and they are considered physically stronger than their women counterparts (Norberg & Johansson, 2021). Similar to the concept of the “ideal worker,” the institution of medicine expects transgender individuals to adopt cisnormative behaviors and punishes those who do not conform to gender‐normative expectations by denying them healthcare services related to gender‐affirming services.…”
Section: Institutional Analysis: Medicine As a Cisgendering Institutionmentioning
confidence: 99%